PENGARUH PARTISIPASI PEMAKAI DAN KETIDAKPASTIAN TUGAS TERHADAP SISTEM INFORMASI AKUNTANSI DENGAN UKURAN ORGANISASI SEBAGAI VARIABEL MODERASI - I Kadek Yudi Swa Andika; Sang Ayu Putu Arie Indraswarawati; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2021)
The purpose of this research is to obtain empirical evidence of the effect of user participation and assignment uncertainty on the performance of accounting information systemi by measuring organization as moderating variable. The research was carried out on the LPD in the Ubudi sub-district. The selection of the samples in this research is using purposive sampling method, with a total of 75 respondents consisting of the Head of the LPD, Administration and the Treasurer. Data collection was carried out by distributing questionnaires. The analysis technique used is multiple line regression analysis and Moderating Regression Analysis (MRA). The results of this research show that: 1) user participation has a positive influence on the performance of SIAi in the Ubudi Sub-district LPD, 2) assignment uncertainty has a negative effect on SIAi performance in Ubudi Sub-district LPD, 3) organizational size has a negative effect on SIAi performance in Ubudi Sub-district LPD, 4) size of organization is able to moderate the influence of user participation on the performance of SIAi in the LPD of Ubudi District, 5) size of organization does not moderate the effect of uncertainty of assignment on the performance of SIAi in the Ubudi sub-district LPD